Emergence of antimicrobial resistance among Acinetobacter species: a global threat. Issue 5 (October 2016) - Clark, Nina M.; Zhanel, George G.; Lynch, Joseph P.
Abstract : Purpose of review: Bacteria within the genus Acinetobacter [principally Acinetobacter baumannii – calcoaceticus complex (ABC)] are Gram-negative coccobacilli that may cause serious nosocomial infections (particularly ventilator-associated pneumonia and infections of the bloodstream, urinary tract, and wounds) as well as community-acquired infections (often skin/soft tissue infections in the context of trauma). Within the past two decades, Acinetobacter spp. have been responsible for an increasing number of infections in intensive care units (ICUs) globally. Treatment of Acinetobacter infections is difficult, as Acinetobacter spp. are intrinsically resistant to multiple antimicrobial agents, and have a remarkable ability to acquire new resistance determinants via multiple mechanisms. Recent findings: Since the 1990s, global resistance to antimicrobials has escalated dramatically among ABC. Global spread of multidrug-resistant (MDR) A. baumannii strains reflects dissemination of a few clones between hospitals, geographic regions, and continents; this spread is amplified by excessive use of antibiotics. Many isolates are resistant to all antimicrobials except colistin (polymyxin E), and some infections are untreatable with existing antimicrobial agents. Summary: Antimicrobial resistance poses a serious threat to control infections due to ABC. Strategies to curtail environmental colonization with MDR-ABD will require aggressive infection control efforts and cohorting of infected patients. Thoughtful antibiotic strategies are essential to limit the consequences and spread of MDR-ABC. Optimal therapy will likely require combination antimicrobial therapy of existing antibiotics as well as development of novel antibiotic classes.